Work-in-Progress-LIVE: Model for Learning in Interactive and Immersive Virtual Environments - Thompson, Brad (2021 7th International Conference of the Immersive Learning Research Network (iLRN), 2021)
Combining immersive environments with intelligent tutoring (ITS) provides synergies that can accelerate learning beyond what is possible individually. The integration of these and other sub-domains represents a new domain-LIVE-conceived through an affordance-based design approach and informed by embodied interaction ideals. Offered as a tutorial model for immersive virtual education, it implements adaptive pedagogical methods to provide social support for tutor-to-student and peer-to-peer instruction in inquiry-based activities (such as science labs). This work-in-progress paper communicates the basic domain definition, its place in the literature, and efforts to create and evaluate a prototype application.